Association between New York and Shanghai markets: evidence from the stock price indices - E. Jarrett, Jeffrey; Sun, Tina (Journal of Business Economics and Management, 2012)
This paper examines the time series characteristics of stock price indices for New York and Shanghai during the period of 1991 to 2009. Specifically, we calculate the rate of return and the volatility of return for two markets and estimate the serial correlation and co-movement of the two markets. We find that the average rate of return in Shanghai is much higher than that in New York while Shanghai stock prices are more volatile than New York stock prices. Further, we find that Shanghai stock prices are positively serially correlated while New York stock prices are negatively serially correlated in terms of auto regression of the rate of return. In the multivariate regressions, we find that there is little evidence to show that either the rate of return in Shanghai would affect the rate of return in New York or the rate of return in New York would affect the rate of return in Shanghai. It suggests that the two markets are not integrated. Last, we studied and made conclusion concerning the volatility of the New York and Shanghai indices relate to each other. Article in English. Niujorko ir Šanchajaus rinkos: akcijų kainų indeksai Santrauka. Šis tyrimas apima akcijų kainų indeksų analizę Niujorko ir Šanchajaus biržose nuo 1991 m. iki 2009 m. Atlikus tyrimus nustatyta, kad vidutinė grąžos norma Šanchajuje yra daug didesnė nei Niujorke, o Šanchajaus akcijų kainos kinta daug sparčiau nei Niujorko vertybinių popierių kainos. Be to, pastebėta, kad Niujorko akcijų kainos turi teigiamą koreliaciją, o Šanchajaus akcijų kainos – neigiamą (lyginant grąžos normą). Atlikę daugiakriterinės regresijos analizę, autoriai pastebėjo, kad Šanchajaus biržose vykstantys grąžos normos pasikeitimai neturi įtakos Niujorko biržoms ir, atvirkščiai, Niujorke vykstantys pasikeitimai neturi įtakos Šanchajaus biržoms. Tai rodo, kad šios dvi rinkos nėra integruotos. Reikšminiai žodžiai: indekso skaičius, kintamumas, koreliacija, Šanchajus vertybinių popierių birža, Niujorko vertybinių popierių birža